Students Perspective on the Use of Rock Song in Learning to Improve Students Vocabulary - Hafizh Alghifari; Sugeng Susilo Adi; Widya Caterine Perdhani (Edu-Ling: Journal of English Education and Linguistics, 2022)
Mastering English vocabulary is important thing to be able to master English. The use of interesting learning media in vocabulary learning has a positive role in the learning process. The purpose of this study was to determine the students perspective on the use of rock song to increase students vocabulary. This research is a descriptive study using a mixed method. The subjects of this study were 70 8th grade students of Shalahuddin Junior High School. This study uses 2 data collection techniques, namely questionnaires and interviews. The results of this study indicate that students' perceptions of the use of rock songs in learning get a positive response from students. The use of rock songs in learning can increase students' learning motivation because the media used is interesting and new for students. In addition, students are easier to remember vocabulary and students are easier to get a lot of new vocabulary contained in the lyrics of the rock song used.